Eksplorasi Dinamika Brand Evangelism: Analisis Mediasi Consumer Perceived Ethicality dan Brand Passion: Studi Kasus pada Starbucks Coffee Bandung) - Rifa’atul Sri Aghnia; Arry Widodo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Consuming coffee has become a lifestyle for people in Indonesia. Nowadays, drinking coffee at outlets is not just a thirst quencher, but it can also be an activity, such as working on assignments, holding meetings with friends or relatives, or just chatting. Starbucks not only offers a coffee experience, but also provides a unique experience that sets it apart from other coffee outlets. They create a different atmosphere by presenting friendly staff and exclusive music that can only be enjoyed at Starbucks. This is what gave birth to the term "Starbucks Experience". This research was conducted to explore how influential Customer Perceived Ethicality, Brand Evangelism, and Brand Passion are on Starbucks Coffee Bandung. The research population was Starbucks Coffee consumers in Bandung City, with 400 respondents taken through distributing online questionnaires through social media. The results showed that brand passion positively and significantly influenced brand evangelism, customer perceived ethicality positively and significantly influenced brand evangelism, customer perceived ethicality positively and significantly influenced the quality of brand passion, and customer perceived ethicality positively and significantly influenced brand evangelism mediated by brand passion.